Efficient removal of cationic dye mixtures from water using a bio-composite adsorbent optimized with response surface methodology. (15th November 2018) - Choudhury, Swastika; Ray, Samit Kumar
Graphical abstract: Highlights: Composite adsorbents were made from poly (NVP-co-AA) and kappa-carrageenan. The polymer was characterized by FTIR, NMR, XPS, BET, DMA, SEM, DTA-TGA, XRD and PZC. Synthesis & process parameters were optimized with CCD of RSM. Competitive adsorption of ST + BCB cationic dye were studied with this adsorbent. The adsorbent showed high adsorption capacity & excellent reusability. Abstract: Bio-composite type functional adsorbents were prepared by integrating kappa-carrageenan (KC) and copolymers of poly (N-vinylpyrrolidone-co-acrylic acid) (CP). The CP was synthesized free radically from its monomers N-vinylpyrrolidone (NVP), acrylic acid (AA) and methylene bis-acrylamide (MBA) crosslinker comonomer in the presence of KC in water. The adsorbents were characterized and used for separation of Safranine T (ST) and brilliant cresyl blue (BCB) cationic dye mixtures from water. The synthesis and process parameters for adsorption were optimized with central composite design (CCD) of the response surface methodology (RSM). Accordingly, the CPKC bio-composite adsorbent with optimized composition of 2.5 wt% of KC, 1.5 wt% of MBA and NVP: AA molar ratio of 1.3:1 showed a high adsorption capacity of 362.5 mg/g for ST and 398 mg/g of BCB dye for a binary mixture containing 100 mg/L each of the dye in a solution pH of 7 and adsorbent dose of 0.25 g/L.